Genotoxicity and antigenotoxicity assessment of shiitake (Lentinula edodes (Berkeley) Pegler) using the Comet assay - Miyaji, CK (2004)
The mushroom shiitake (Lentinula edodes (Berkeley) Pegler) is been widely consumed in many countries, including Brazil, because of its pleasant flavor and reports of its therapeutic properties, although there is little available information on the genotoxicity and/or antigenotoxicity of this mushroom. We used the Comet assay and HEp-2 cells to evaluate the in vitro genotoxic and antigenotoxic activity of aqueous extracts of shiitake prepared in three different concentrations (0.5, 1.0 and 1.5 mg/mL) and three different temperatures (4, 22 and 60 °C), using methyl methanesulfonate (MMS) as a positive control and untreated cells as a negative control. Two concentrations (1.0 and 1.5 mg/mL) of extract prepared at 4 °C and all of the concentrations prepared at 22 ± 2 and 60 °C showed moderate genotoxic activity. To test the protective effect of the three concentrations of the extracts against the genotoxicity induced by methyl methanesulfonate, three protocols were used: pre-treatment, simultaneous-treatment and post-treatment. Treatments were repeated for all combinations of preparation temperature and concentration. Two extracts (22 ± 2 °C 1.0 mg/mL (simultaneous-treatment) and 4 °C 0.5 mg/mL (post-treatment)) showed antigenotoxic activity.